Understanding an organic cluster from the perspective of different stakeholders : an integrated look - Lopes, Cynthia Mikaela Chemello Faviero (2018)
The increase in organic production and consumption demonstrates a movement in favor to alternative forms of food production, aiming to achieve modes that provide health and wellbeing for the producers and consumers, together with environmental preservation. People’s interest in organically produced food is increasing worldwide. Even so, many challenges are faced by the producers, and in this context new forms of organization appear in this market: clusters. The cluster constitute a way to gain competitiveness. In order to explore and better understand this phenomenon, this dissertation aimed, as main objective, to understand the formation of an organic cluster from the perspective of different stakeholders. Through a single embedded case study, this research had a qualitative approach, being the exploratory type. A research protocol along with other cautions in order to gain rigor in the qualitative research. The data were collected through documentary research, in-depth interviews and participatory observations, and analysed through content analysis. As evidence resulting from this study, the following points are highlighted: (1) it was possible to map the cluster and the relations established by the agents; (2) the main drivers of the cluster are mostly related to the pioneerism, institutionalization of the arrangement and its form of management. The barriers are mostly the lack of prepare to deal with tourists, and the marketing initiatives were considered both as a driver and a barrier, since needs to be better developed, but even incipient has some actions established; (3) the main motivations and barriers for the agents to work with organics were confirmed from the literature. The will to educate the consumers, although, was an interesting finding, as one of the drivers; (4) four pillars were identified as fundamental for the cluster, and their structuration and fortification might help the development of the arrangement: to product, to preservate, to show and to educate.